Understanding the attitude and repurchase intention towards halal food product among non-muslim consumers in Malaysia - Ag. Damit, Dayang Haryani Diana (2019)
The purpose of this study was to understand the factors that influence the attitude and repurchase intention of non-Muslim consumer in Malaysia towards Halal food product. This study highlighted the conceptual insights of the multidimensional constructs of buyer factors (i.e. religion adoption, lifestyles, halal awareness, consumers past experience); and the product attribute factors (i.e. halal logo, perceived product quality and product country-of-origins) on the attitude of non-Muslim consumer on Halal food product. The study also examined the influence of non-Muslim consumer attitude on Halal food and subjective norm as the independent variables to the repurchase intention of non-Muslim consumer towards Halal food product. Thus, this study investigated the mediating effect of consumer trust between product attribute factors and the attitude of non-Muslim consumer on Halal food product. In addition, two theoretical lenses-the Theory of Planned Behaviour and Model of Buyer Behaviour are utilized in this study to explain the influence buyer factors and product attribute factors to non-Muslim attitude on Halal food product; and the influence of attitude and subjective norm to repurchase intention of non-Muslim consumers toward halal food product in Malaysia. Results from a survey of 444 Non-Muslim consumers whom have prior experience of consuming Halal food product were used for the statistical analysis. The data were drawn from five (5) states in Malaysia which consist of Pahang, Penang, Selangor, Johor and Sabah. Smart Partial Least Square 3.0 was used to analyse the data. The findings revealed that the buyer factors of religion adoption and consumer past experience influence the attitude of non-Muslim consumer towards halal food product. This study empirically proved that product attributes factors (i.e. halal logo, perceived product quality, and product country-of-origin) positively influence the attitude of non-Muslim consumer towards halal food product. The finding of the study also evident the attitude of non-Muslim consumer towards halal food product and subjective norm does influence non-Muslim consumers‘ repurchase intention of the halal food product. Finally, mediation analysis results show that consumer trust mediated the path between the influence of product factors (halal logo, product country-of-origin, and perceived product quality) and the attitude of non-Muslim consumer towards halal food product. More importantly, this study has provide further insights into the non-Muslim consumers‘ attitude and intention behaviour towards halal product as well as the prospect of halal industry in Malaysia.